Teologi Islam Perspektif Sayyid Qutb - Lingga Yuwana (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2020)
Abstract:This paper particularly discusses Sayyid Qutb's concept of Islamic Theology. In this paper exposed Sayyid’s ideas that many people said, are the main concept from Sayyid Qutb that inspire thinking for many “radical” groups. Even James Toth said that Sayyid Qutb as the architect of a mindset that inspired the 9/11 tragedy. The argument was reinforced by Paul Berman, who called Sayyid Qutb as The Philosopher of Islamic Terror. From these two arguments, it is obvious that Sayyid’s figure is highly controversial and is a subject of research for many scholars. Even Sayyid’s work, which was titled Ma’alim fii Ath-Thariq, was part of a forbidden book used by the Egyptian government to sentencing Sayyid to death in 1966. The study in this paper is library research by using a descriptive-philosophical analysis. From the results of this research, it can be inferred that Sayyid’s thinking is composed of several ideas. (1) Jahiliyyah. (2) Ratio and Revelation. (3) Islam, Tauhid and Islamic Brotherhood (Ukhuwah Islamiyah), which consists of ukhuwah bil ubudiyyah, ukhuwah bil insaniyyah, ukhuwah bil wathaniyyah, and ukhuwah fii Din Al-Islam. Those concepts were important as another basis for Sayyid’s political views, religion (Ad-Din), and ideological concept, which is the most important goals for banishing jahiliyyah thinking like communism, capitalism, and other concepts based on materialism got into Islam. Keywords: Sayyid Qutb, Islam, Jahiliyah, Ukhuwah Islamiyah